(untitled) (Research, Society and Development, 2022)
The construction of environmental indicators has allowed improving management models of natural resources through the evaluation of measures adopted and the monitoring of strategic actions to be used in the search for sustainable development. This work aimed at the construction and evaluation of indicators related to changes in carbon behavior due to changes of vegetation cover in the southern cerrado of Tocantins. The methodology adopted was from the OECD (Organization for Economic Cooperation and Development), the Pressure-State-Impact/Effect-Response (PSI/ER) framework, for the construction of a matrix. For the validation of indicators, specific methodologies were used according to technical standards. The proposed matrix considers the following indicators: soil carbon, carbon stocks in humic fractions, labile carbon - C-Labile and carbon stocks in light organic matter - LOM. The use of indicators presented in this work is of great importance for the monitoring of carbon caused by changes in vegetation cover in the southern cerrado of Tocantins, as a subsidy for policies and actions aimed at reducing the impacts of environmental degradation.